Investigating The Antecedents of Brand Loyalty Mediated by Green Trust and Green Satisfaction Empirical Study in Central Java - Muhammad Ariq Sofyan; Kardison Lumban Batu (Diponegoro Journal of Management, 2023)
ABSTRACT An effective strategy in generating customer loyalty is to make consumers believe and be satisfied with the products and actions of the company. To make consumers believe, companies need to pay attention to greenwashing, green perceived value, eco-brands and eco-labels. The purpose of present study is to design and develop an empirical conceptual model of how greenwashing, green perceived value, eco-brand, and eco-label affect brand loyalty through green trust and green satisfaction as mediating variables. This study uses Panasonic consumers as the research population, then sampling is carried out using purposive sampling and has several criteria. The sample in this study was 150 respondents who live in Central Java. The collected data will be analysed using the structural equation model (SEM) method and processed with AMOS software. The results of this study indicate that greenwash has a significant negative effect on green trust, green perceived value has a significant positive effect on green trust, eco-brand has a significant positive effect on green trust, eco-label has a significant positive effect on green trust, greenwash has no effect on green satisfaction, green perceived value has no effect on green satisfaction, eco-brand has no effect on brand loyalty, green trust has a significant positive effect on brand loyalty, dan green satisfaction has a significant positive effect on brand loyalty